Clinical features of newly diagnosed cytomegalovirus retinitis in Northern Thailand - Somsanguan Ausayakhun (2018)
Purpose: To characterize the clinical manifestations of cytomegalovirus (CMV) retinitis in northern Thailand. Design: Prospective, observational, cross-sectional study. Methods: We recorded characteristics of 52 consecutive patients newly diagnosed with CMV retinitis at a tertiary university-based medical center in northern Thailand. Indirect ophthalmoscopy by experienced ophthalmologists was supplemented with fundus photography to determine the proportion of eyes with various clinical features of CMV retinitis. Results: Of the 52 patients with CMV retinitis, 55.8% were female. All were HIV-positive. The vast majority (90.4%) had started antiretroviral therapy. CMV retinitis was bilateral in 46.2% of patients. Bilateral visual acuity worse than 20/60 was observed in 23.1% of patients. Of 76 eyes with CMV retinitis, 61.8% had zone I disease and 21.6% had lesions involving the fovea. Lesions larger than 25% of the retinal area were observed in 57.5% of affected eyes. CMV retinitis lesions commonly had marked or severe border opacity (47.4% of eyes). Vitreous haze often was present (46.1% of eyes). Visual impairment was more common in eyes with larger retinitis lesions. Retinitis lesion size, used as a proxy for duration of disease, was associated with fulminant appearance (odds ratio, 1.24; 95% confidence interval, 1.01 to 1.51) and marked or severe border opacity (odds ratio, 1.36; 95% confidence interval, 1.11 to 1.67). Based on lesion size, retinitis preceded antiretroviral treatment in each patient. Conclusions: Patients seeking treatment at a tertiary medical center in northern Thailand had advanced CMV retinitis, possibly because of delayed diagnosis. Earlier screening and treatment of CMV retinitis may limit progression of disease and may prevent visual impairment in this population. © 2012 Elsevier Inc. All Rights Reserved.